An efficient method for structural coupling of mechanical systems by using frequency response functions - Sen, Murat; cakar, Orhan (Sage Publications Ltd, 2024)
In many mechanical systems, it is very common to bring together different structural elements or subsystems produced by different producers and create a whole coupled system. It is often not possible to manufacture an entire mechanical system in one place. Although the dynamic properties of each of the subsystems produced by different manufacturers are known, it is a matter that should be known and studied how the dynamic behavior of the new system will be after the creation of a new system by combining these subsystems. In this study, a method for structural coupling of mechanical systems is presented in order to contribute to the solution of structural dynamic problems. It is based on Sherman-Morrison formula known for solving mathematical inverse problems of modified matrices. The method is very useful and practical for real mechanical engineering applications due to only the frequency response functions belong to the coupling coordinates of the subsystems are used. The main highlight of the presented method is there is no need a matrix inversion for calculations.
Keywords: structural coupling; frequency response function; Sherman-Morrison formula; structural modification; substructuring